What are the factors affecting the recovery rate of bronchoalveolar lavage fluid?. (6th December 2021) - Shikano, Kohei; Abe, Mitsuhiro; Shiko, Yuki; Tsushima, Kenji; Yoshioka, Keiichiro; Ishiwata, Tsukasa; Kawasaki, Takeshi; Ikari, Jun; Terada, Jiro; Kawasaki, Yohei; Tatsumi, Koichiro
Abstract: Background: Bronchoalveolar lavage (BAL) is a useful examination for the evaluation of interstitial lung disease. A high BAL fluid (BALF) recovery rate is desirable because low recovery rates lead to inaccurate diagnoses and increased adverse events. Few studies have explored whether BALF recovery rates are influenced by clinical factors. Objectives: This study aimed to identify the clinical parameters affecting the recovery rates of BALF and the extent of their effects. Method: Data from patients who underwent BAL at the Chiba University Hospital between 2013 and 2019 were retrospectively reviewed. BAL was performed with three aliquots of 50‐ml physiological saline. The potential association of the BALF recovery rate with clinical parameters such as age, sex, smoking status, underlying disease, bronchus used for the procedure and pulmonary function, was analysed. Results: Eight hundred twenty‐six patients had undergone BAL. The average recovery rate was 52.4%. Factors affecting BALF recovery rates included male sex (odds ratio [OR]: 0.32, 95% confidence interval [CI]: 0.20–0.53, p  < 0.001); age ≥ 65 years (OR: 0.50, 95% CI: 0.33–0.76, p  < 0.001); use of the left bronchus (OR: 0.46, 95% CI: 0.30–0.71, p  = 0.001) and bronchi other than the middle lobe bronchus or lingula (OR: 0.41, 95% CI: 0.25–0.65, p  < 0.001); and forced expiratory volume in 1 s divided by forced vital capacity <80% (OR: 0.42, 95% CI: 0.40–1.00, p  < 0.001). Conclusion: Sex, age, bronchus used for the procedure and pulmonary function may be useful as pre‐procedural predictors of BALF recovery rates.